Reflections About the Role of Intellectuals in Latin America Reflexiones acerca del rol de los intelectuales en América Latina Reflexões sobre o papel dos intelectuais na América Latina - Judith Naidorf; Alejandra Beatriz Martinetto; Silvina Andrea Sturniolo; Julieta Armella (Arizona State University, 2010)
The purpose of this paper is to address some theoretical aspects - concepts that contribute to reflection on the specific role of the current Latin American intellectual. The contributions of various authors will help us to characterize a role that is constantly rethinked, analyzed and disputed. The proposal is to retake the theoretical developments in the category "intellectual" from Antonio Gramsci and Immanuel Wallerstein mainly, but making reference to its most intense moments in the 60-70 decades with Sartre and Foucault in Europe. It also highlights the contributions made by Pierre Bourdieu, Sousa Santos and the contributions to Latin America by Fals Borda, Florestan Fernandez, Octavio Ianni and Eliseo Veron, among others. Also included are examples of statements for the EZLN by Subcomandante Marcos and refers to the analysis performed by Julio Gambina and Daniel Campione for the Argentine case. It’s not the interest of this work to arrive at definitions finished about the social function of intellectual debate but to contribute to a not new but always applicable, which should be a breakthrough for each of our practices in the different social areas in which we daily work. En este trabajo nos proponemos abordar algunos aspectos teórico - conceptuales que contribuyan a la reflexión sobre la especificidad del papel del intelectual latinoamericano actual. Los aportes de diversos autores nos ayudarán a caracterizar un rol que se encuentra en permanente reformulación, análisis y discusión. La propuesta es retomar los desarrollos teóricos de la categoría de intelectual, desde Antonio Gramsci e Immanuel Wallerstein principalmente, pasando por sus momentos más intensos en la década del 60-70 con Sartre y Foucault en Europa. También se rescatan las contribuciones realizadas por Pierre Bourdieu, Sousa Santos y los aportes para América Latina de Fals Borda, Florestán Fernández, Octavio Ianni y Eliseo Verón, entre otros. Además se incluyen como ejemplos declaraciones del subcomandante Marcos para el EZLN y se hace referencia a los análisis realizados por Julio Gambina y Daniel Campione para el caso argentino. No es interés de este trabajo arribar a definiciones acabadas acerca de la función social del intelectual sino aportar a un debate no nuevo pero siempre vigente. Neste trabalho pretendemos abordar alguns aspectos teóricos-conceituais que contribuem para a reflexão sobre especificidade do papel do intelectual latino-americano atual. As contribuições de diferentes autores nos ajudam a caracterizar um papel que está constantemente sendo repensado, a análisado e discutido. A proposta é revisitar aos desenvolvimentos teóricos sobre o "intelectual" de Antonio Gramsci e Emanuel Wallerstein principalmente através dos debates mais intensos na década de 60-70 com Sartre e Foucault na Europa. Também se destacam as contribuições feitas por Pierre Bourdieu, Sousa Santos e contribuições desde América Latina de Fals Borda, Florestan Fernandes, Octavio Ianni e Eliseu Veron, entre outros. Também estão incluídos como exemplos declarações do subcomandante Marcos do EZLN e referências aos análises realizadas por Julio Gambina e Daniel Campione para o caso argentino. Este trabalho não pretende chegar a definições acabadas sobre a função social do intelectual, mas contribuir ao debate que não e novo, mas ainda tem vigencia.